Natural disaster shock, risk aversion and corn farmers' adoption of degradable mulch film: evidence from Zhangye, China. Issue 1 (29th January 2021) - Si, Ruishi; Aziz, Noshaba; Liu, Mingyue; Lu, Qian
Abstract : Purpose: Degradable mulch film (DMF) is a potential alternate to polyethylene (PE) mulching. In this regard, the purpose of this paper is to explore the effects and paths of natural disaster shock and risk aversion influencing farmers' DMF adoption. Design/methodology/approach: This research is conducted by collecting cross-sectional data of corn farmers in Zhangye, China. First, by using the Tobit model, the paper attempts to explore the effects of natural disaster shock and risk aversion influencing farmers' DMF adoption. Second, IV-Tobit model is applied to deal with endogenous problems between risk aversion and DMF adoption. Additionally, the researchers used a moderating model to analyze feasible paths of natural disaster shock and risk aversion impacting farmers' DMF adoption. Findings: The outcomes show that natural disaster shock and risk aversion significantly and positively affect farmers' DMF adoption. Though risk aversion plays a significant moderating effect in influencing farmers' DMF adoption by natural disaster shock, the moderating effect has a serious disguising effect. By considering the heterogeneity of risk aversion, the paper further confirms that if the intensity of natural disaster shock is increased by one unit, the intensity of MDF adoption by farmers with high-risk aversion also tends to increase by 15.85%. Originality/value: This study is the pioneer one, which is evaluating the intensity of farmers' DMF adoption from adoption ratio, investment amount, labor input and adoption time. Additionally, the research provides important guidelines for policymakers to motivate medium and low-risk aversion farmers to adopt DMF.